A review of therapeutic agents and Chinese herbal medicines against SARS-COV-2 (COVID-19). (August 2020) - Huang, Fangfang; Li, Ying; Leung, Elaine Lai-Han; Liu, Xiaohua; Liu, Kaifeng; Wang, Qu; Lan, Yongqi; Li, Xiaoling; Yu, Haibing; Cui, Liao; Luo, Hui; Luo, Lianxiang
Graphical abstract: Abstract: The epidemic of pneumonia (COVID-19) caused by novel coronavirus (SARS-CoV-2) infection has been listed as a public health emergency of international concern by the World Health Organization (WHO), and its harm degree is defined as a global "pandemic". At present, the efforts of various countries focus on the rapid diagnosis and isolation of patients, as well as to find a treatment that can combat the most serious impact of the disease. The number of reported COVID-19 virus infections is still increasing. Unfortunately, no drugs or vaccines have been approved for the treatment of human coronaviruses, but there is an urgent need for in-depth research on emerging human infectious coronaviruses. Clarification transmission routes and pathogenic mechanisms, and identification of potential drug treatment targets will promote the development of effective prevention and treatment measures. In the absence of confirmed effective treatments, due to public health emergencies, it is essential to study the possible effects of existing approved antivirals drugs or Chinese herbal medicines for SARS-CoV-2. This review summarizes the epidemiological characteristics, pathogenesis, virus structure and targeting strategies of COVID-19. Meanwhile, this review also focus on the re-purposing of clinically approved drugs and Chinese herbal medicines that may be used to treat COVID-19 and provide new ideas for the discovery of small molecular compounds with potential therapeutic effects on novel COVID-19.